Synthesis and magnetic studies of copper(II)-lanthanide(III) 5-bromosalicylideneglycylglycine - Cristóvão, Beata; Ferenc, Wieslawa; Sarzyński, Jan; Głuchowska, Halina (Eclética Química, 2009)
The physico-chemical properties of the new 3d-4f heteronuclear complexes with general formula LnCu3(C11H8N2O4Br)3·13H2O (where Ln = Pr, Eu, Gd, Tb, Er, Yb and H3(C11H8N2O4Br) – 5-bromosalicylideneglycylglycine) were studied. The compounds were characterized by elemental, spectral and thermal analyses and magnetic measurements. The formation of Schiff base is evidenced by a strong band at ca. 1646–1650 cm–1 attributable to C=N stretching mode. The presence of water molecules is confirmed by broad absorptions with maximum at 3360 – 3368 cm-1. The Cu(II)–Ln(III) complexes are stable up to ca. 318 K. During dehydration process the water molecules are lost probably in two stages. The magnetic susceptibility data for these complexes change with temperature according to the Curie-Weiss law.